Caminhos para práticas pedagógicas inovadoras de ensino e aprendizagem: uma análise a partir dos I e II Seminários Web Currículo - Ribeiro, Renata Aquino (2012)
Standards and practices in education and technology on the web are still themes not very often discussed among Brazilian educators. The goals of this research include the identification of characteristics of innovative practices regarding the integration of technologies in the curriculum, the analysis of the publications of the Seminars Web Curriculum aiming to find categories for innovative practices, a panorama of the publications on Web Curriculum blog from 2008 to 2011, evidentiating publications related to the themes discussed and relevant between the participants of the research group in technologies in educaton, identifying elements which indicate an innovative use of technologies in education integrated with the curriculum, based on the practices reported in the documentation of the Seminars Web Curriculum and the textos in the blog related to the events. The methodology of selection of data and analysis of results used a software of qualitative research named CHIC and analysis of content beyond the documental data (blog and articles sent to I and II Seminars Web Curriculum). The experience of editing the online documentation of the I and II Seminar Web Curriculum PUC-SP made possible to examine several of these ideas, beyond the proposed paths of the Post-Graduate Program which promoted the activity. In 2008, the I Seminar Web Curriculum PUC-SP happened with the support of the program aforementioned and brought as theme the integration of technologies of communication and information to the curriculum. The context of the panorama of these practices, bearing in mind the larger implications of the use of the web in Web Curriculum, and their analysis are the goals of this investigation. In the year 2010, the II Seminar Web Curriculum expanded the proposal with the use of social networks and metaverses. The edition of the blog Web Curriculum and of the Twitter during the two first editions of the event have brought valuable discoveries about the importance that researchers and teachers see in the integration of technologies of information and communication to the curriculum and the studies related to it. The results of this research have brought the identification of characteristics of innovative practices pertaining to the integration of web technologies into the curriculum and the analysis of the publications of I and II Seminars Web Curriculum with the proposition of categories to aid mapping the tendencies for innovative practices